Lymphoid Polyposis in an Adult Male- A Case Report - Islam, Shamina; Choudhury, Tamanna; Hossain, Md Shahadat; Kamal, Mohammed (Bangabandhu Sheikh Mujib Medical University Journal, 2011)
Benign lymphoid polyposis is a rare histologic entity and should not be confused with malignant disease of the colon and rectum. We present a case of lymphoid polyposis in the intestine in a 26 years old male patient who was admitted for the treatment of faecal fistula. He had history of appendectomy, followed by ileostomy four years back. Physical examination revealed multiple faecal fistulae in the right lower abdomen. Right-sided hemicolectomy was done. Gross examination showed multiple polyps through out the specimen; the junction between caecum and ascending colon was found partially stenosed. Microscopy revealed polypoid structures consisting of multiple lymphoid follicles with prominent germinal centers. A stenosed area represented probable fistulous tract within the fibrosis. The final diagnosis was lymphoid polyposis based on clinical, gross and microscopic features. Keywords: Lymphoid polyposis; Faecal fistula. DOI: http://dx.doi.org/10.3329/bsmmuj.v4i2.8643 BSMMU J 2011; 4(2):119-121